A Study of Google Docs Learning Media on Creative Thinking Skills and Student Learning Outcomes in Social Studies in Junior High Schools - Novitasari, Siti; Hanif, Muhammad; Parji, Parji (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study investigates the effectiveness of Google Docs as an innovative learning medium in enhancing students’ creative thinking skills and learning outcomes in Social Studies learning at the junior high school level. Methodology: A quantitative approach was employed using a quasi-experimental posttest non-equivalent control group design. The participants consisted of 28 eighth-grade students from Junior High School Negeri 12 Madiun, divided into an experimental group (n = 14) that used Google Docs for learning activities and a control group (n = 14) that used traditional textbook-based learning media. Data were collected through a creative thinking questionnaire and a learning outcomes test, and then analyzed using descriptive statistics and independent-samples t-tests at a 0.05 significance level. Main Findings: The results indicate that students in the experimental group achieved significantly higher levels of creative thinking and learning outcomes than those in the control group. The independent-samples t-test results revealed significant differences in creative thinking skills (t = 6.957, p < 0.05) and learning outcomes (t = 5.924, p < 0.05). These findings demonstrate that Google Docs effectively promotes collaborative learning, active engagement, and higher-order thinking skills. Novelty/Originality of this study: This study provides empirical evidence that integrating collaborative digital tools, such as Google Docs, can improve both cognitive achievement and creative thinking in junior high school Social Studies.